Konsepsi dan Karakteristik Arsitektur Islam pada Bangunan Pesantren Indonesia - Aufarul Maulidy Taufikillah; Arigan Wicaksa (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This study examines the concepts and characteristics of Islamic architecture applied to pesantren buildings in Indonesia. Using a qualitative approach with a descriptive method through comprehensive literature study, this research analyzes how Islamic architectural principles adapt and synergize with local architecture in the context of traditional to modern pesantren. The findings show that pesantren architecture in Indonesia is a unique manifestation of the fusion of Islamic values with local culture, reflected in seven key elements: the practice of Islam as a way of life, qibla orientation, the concept of hijab, interiors supporting Islamic values, Islamic decorative arts, Islamic values in protection, and the design of dormitories supporting the development of Islamic awareness. The evolution of pesantren architecture has led to various typologies, ranging from traditional to modern forms, each reflecting the adaptation of Islamic architectural principles to the needs of education and the progression of time. This study reveals that despite significant design evolution, pesantren continue to uphold the essence of fundamental Islamic architectural values in every aspect of their design.